Akulturasi Islam dan Budaya Lokal Kajian Historis Sejarah Dakwah Islam di Wilayah Rejang - Mabrur Syah (Jurnal Dakwah dan Komunikasi, 2016)
This study intends to determine, (1) Origin of Rejang (2) History entry of Islam in the region Rejang (3) Islam and Indigeneous Culture Acculturation Rejang.This study is a qualitative research, with a historical approach (historical aproach)Of the studies that have been done, we can conclude the following matters; (1). There are two Opinions about the origin of Rejang, First Rejang is derived from the Indian tribe Rear (Semenajung Vietnam) is inspired by the ancestors of Indonesia from the boat people coming from India Rear seeking new areas all the archipelago. Both Rejang derived from Indochina Tonkin, they moved to Sumatra through sailing towards Sarawak Borneo (North Borneo) about 1200 years ago. Sarawak they sailed past the island of Bangka Belitung towards the river Musi, then deviated to right toward the river Rawas up in the most upstream Rawas. Most live in this area and some sail down the river to get to the mountain Rawas Tapus Hulu, and settled there. (2). Islam has been entered in Rejang Lebong the 15th century Sultan Muzafar Through marriage Shah (King Indrapura) with Princess serindang Moon. (3). Assimilation between Islam that is Universal with culture that is reality, spawned a distinctive cultural acculturation Islam, Acculturation covering almost the entire social order Rejang ranging from attitudes, behaviors and customs that have been stained with the values of Islam.